Explanation of the Viewpoint of Dental Students Towards the Study Guide of the Oral Medicine Course - SH Shirazian; A Mansourian; M Vatanpour; N Ghasemi (Islamic Azad University, 2017)
Background and aim: Study guide is a tool for establishing the student-centered learning process. It is an assortment for directing the student in the management of his learning by foreseeing educational obligations, aims and contents. Considering the important role of study guides in students' learning process, the aim of the present study was to explain the point of view of dental students towards the study guide of the oral medicine course. Materials and methods: This study was performed in two phases: 1-compilation of a study guide for the practical oral medicine course, and 2- implementation of the study guide by 73 dental students, evaluation of their point of view towards its items, and also estimation of their level of satisfaction. Results: 48.6% of the participants were completely satisfied, 18.1% were moderately satisfied; whereas, 6.9% were unsatisfied with the study guide. 26.4% of the students had left the open questions unanswered. 71.2% of the students needed some examples for implementing theoretical lessons in the clinical setting. Few students felt the need to know about the role of the department's personnel.   Conclusion: A high percentage of the students were moderately or completely satisfied with the study guide. They believed that the study guide has improved their learning process, and has even resulted in higher final scores. Knowing the opinion of students is useful for revision and improvement of the study guide.